Pengembangan Sistem E-Commerce Berbasis Web untuk Meningkatkan Daya Saing UMKM di Pasar Digital - Indra Oktavian; Edy Susena (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This article discusses the development of an e-commerce website for a batik store as an effort to digitize marketing and improve operational efficiency. The study focuses on system development strategies, integration of essential features such as product catalogs, shopping carts, digital payment methods, and their impact on customer accessibility. A descriptive qualitative approach was used, employing observation, interviews with the store owner, and a literature review related to e-commerce and digital marketing for MSMEs. The analysis results show that the implementation of a web-based digital platform can expand market reach, enhance customer convenience in shopping, and support more organized and structured transaction recording. The website development was carried out using the Waterfall method to ensure a step-by-step and structured process. These findings indicate that digital transformation through an e-commerce website is a strategic solution for batik MSMEs in facing modern market challenges.